Periodontal Treatment Is Associated With Improvement in Gastric Helicobacter pylori Eradication: An Updated Meta-analysis of Clinical Trials - Ayla Ozturk (Elsevier, 2021)
Objectives: The efficacy of conventional systemic antibiotic therapy for eradication of Helicobacter pylori has been seriously challenged by antibiotic resistance. Identification of alternative therapeutic strategies might help to overcome this limitation. The aim of this study was to update previous meta-analyses that investigated the effect of periodontal treatment on gastric H. pylori eradication. Methods: A systematic electronic search of the literature was conducted to identify all published clinical trials that compared the effect of adjunct periodontal treatment on conventional systemic H. pylori eradication therapy. Results: The updated analysis (consisting of 541 participants representing six studies) demonstrated that, compared with conventional systemic eradication therapy alone, the addition of periodontal treatment resulted in improvements in gastric H. pylori eradication rates with OR 4.11 (P = 0.01). Moreover, not to lose any data, the previously presented Chinese results that could not be assessed by any available mechanism deduced from previously published meta-analysis and with other records were re-analysed. Similarly, the second meta-analysis adding up to a final cluster of 10 studies (909 participants) gives further credence to periodontal treatment as a useful concomitant therapy in the H. pylori eradication therapy (odds ratio [OR] = 2.65; P = 0.0002). Finally, the meta-analysis of four trials consisting of 177 cases and 161 controls showed that periodontal treatment also improved non-recurrence rates of gastric H. pylori infection, with an OR of 5.36 (P-value = 0.0002). Conclusion: Although the inclusion of five additional clinical trials in this updated meta-analysis has not changed the result of the previous review, the current meta-analysis is superior for having removed one study involving the use of chlorhexidine, which did not meet appropriate criteria for inclusion. Our results strengthen the value of periodontal treatment as an adjunctive remedy. Consistency of these results suggests that the incorporation of professional periodontal treatment with systemic eradication therapy may be a wise strategy, enhancing the efficacy of H. pylori eradication therapy. Systematic review registration: in PROSPERO ID number: CRD42019119347.